The Effects of General Inflation and Idiosyncratic Cost Shocks on Within-Commodity Price Dispersion: Evidence from Microdata - Beaulieu, Joe; Mattey, Joe (The Review of Economics and Statistics, 1999)
This study investigates the dispersion of price levels within highly disaggregated markets by examining plant-level product records from the U.S. Census of Manufactures. The paper estimates the effects of inflation on price dispersion through cross-sectional variation in the drift rate of average input costs within a market, arguing that, in several models that relate inflation to price dispersion, the effects of cost increases on dispersion is similar to the effects of general inflation. We also disentangle the effects of aggregate and idiosyncratic shocks on price dispersion. In general, we find that the higher the drift rate of input costs of a given commodity, the larger the amount of price dispersion. The standard deviation of idiosyncratic shocks also is positively correlated with the degree of price dispersion.